Economic Policy Transformation to Drive Sustainable Growth in the Golden Era of Indonesia 2045 - Syavitra, Tomi (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
In 2045, Indonesia has a vision to achieve Golden Indonesia. This is Indonesia’s ideal to become a country recognized in the global arena. One strategy to achieve this is to implement economic policies that focus on structural transformation, which not only rely on investment in human resource development, but also support for strengthening economic investment in technological innovation and education. This study looks at the experiences of various countries such as China, India, and South Korea in implementing economic policies, which are used as material for formulating economic policy transformation strategies in Indonesia. The purpose of this study is to explore the various approaches taken by these countries to achieve economic transformation towards Golden Indonesia 2045. The research approach used is qualitative with descriptive methods, with literature study data collection techniques. The research analysis used is thematic analysis with the discovery of patterns, opportunities, and challenges in implementing economic policies in Indonesia. The results of the study show that Indonesia needs to focus on several aspects of transformation, namely infrastructure investment, increasing agricultural productivity, developing Special Economic Zones (SEZ), increasing exports and diversifying economic products, and investing in education and technological innovation. The main challenge faced in implementing this policy is the consistency of policy implementation which often has an impact on regional disparities and the potential for social resistance to change. This research recommendation makes it necessary for synergy between the government, private sector and society to realize economic transformation in order to realize the vision of Golden Indonesia 2045.